2001
DOI: 10.1111/j.1096-0031.2001.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeny of the Gasterosteidae: Combining Behavioral and Morphological Data Sets

Abstract: Genealogical relationships among the five genera of stick-the subject of intense experimental and theoretical inleback (Gasterosteidae: Smegmomorpha) fishes were vestigation for more than 60 years (Pelkwijk and Tinreconstructed based upon 47 behavioral and 89 morpho- bergen, 1937;Wootton, 1976Wootton, , 1984, and references logical characters. Phylogenetic systematic analysis of therein), which has led to the accumulation of an extenthe combined data set produced a single MPT (consis-sive behavioral, morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Specimens from the Royal Ontario Museum were examined under a Zeiss SV8 stereo-zoom dissecting microscope and character states assigned under the expert guidance of R. Winterbottom (see Appendix 1 for accession numbers). This examination revealed that G. wheatlandi showed the plesiomorphic condition for the following characters listed in McLennan and Mattern (2001): character 6 (broad horizontal median plate on median ethmoid) and character 47 (posterolateral lamina over scapular foramen in cleithra absent). Gasterosteus wheatlandi had the apomorphic condition in two characters, character 10 (interorbital commissures in frontals absent) and character 36 (preoperculo-mandibular canals in dentary absent).…”
Section: Changes To the Data Setsmentioning
confidence: 98%
See 3 more Smart Citations
“…Specimens from the Royal Ontario Museum were examined under a Zeiss SV8 stereo-zoom dissecting microscope and character states assigned under the expert guidance of R. Winterbottom (see Appendix 1 for accession numbers). This examination revealed that G. wheatlandi showed the plesiomorphic condition for the following characters listed in McLennan and Mattern (2001): character 6 (broad horizontal median plate on median ethmoid) and character 47 (posterolateral lamina over scapular foramen in cleithra absent). Gasterosteus wheatlandi had the apomorphic condition in two characters, character 10 (interorbital commissures in frontals absent) and character 36 (preoperculo-mandibular canals in dentary absent).…”
Section: Changes To the Data Setsmentioning
confidence: 98%
“…Bowne did not examine the osteology of Gasterosteus wheatlandi, so this created many missing entries in the data set. In this study we examine the state for four characters that appear to be synapomorphies for Gasterosteus (McLennan and Mattern, 2001), based upon computer extrapolation from missing character codes for G. wheatlandi. Specimens from the Royal Ontario Museum were examined under a Zeiss SV8 stereo-zoom dissecting microscope and character states assigned under the expert guidance of R. Winterbottom (see Appendix 1 for accession numbers).…”
Section: Changes To the Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the degree of red coloration of male sticklebacks appears to signal both direct and indirect benefits to females, at least in those populations where correlations exist. The stickleback family (Gasterosteidae) is relatively small, comprising only five genera (McLennan & Mattern 2001). Not all stickleback species exhibit distinctive nuptial coloration, but it is…”
Section: Introductionmentioning
confidence: 99%